#### notes

a and b are the roots of the equation ax^{2} + bx + c = 0 then,

(1)`alpha+beta=(-b+sqrt(b^2-4ac))/(2a)+(-b-sqrt(b^2-4ac))/(2a)`

`=(-b+sqrt(b^2-4ac)-b-sqrt(b^2-4ac))/(2a)`

`=-(2b)/(2a)`

`therefore alpha+beta=-b/a`

(2) `alphaxxbeta=(-b+sqrt(b^2-4ac))/(2a)xx(-b-sqrt(b^2-4ac))/(2a)`

`=((-b+sqrt(b^2-4ac))xx(-b-sqrt(b^2-4ac)))/(4a^2)`

`=(b^2-(b^2-4ac))/(4a^2)`

`=(4ac)/(4a^2)`

`=c/a`

`therefore alpha beta=c/a`

Ex. (1) If a and b are the roots of the quadratic equation 2x^{2} + 6x - 5 = 0, then find (a + b) and a × b.

Solution : Comparing 2x^{2} + 6x - 5 = 0 with ax^{2} + bx + c = 0.

∴a = 2, b = 6 , c = -5

∴a + b = -b/a = -6/2 = -3

and a × b =c/a =−5/2

#### Video Tutorials

#### Shaalaa.com | Relationship between roots and coefficients of a quadratic equation (1)

##### Series 1: playing of 2

to track your progress

1

0%